Tri-orchidism: A rare case report - Abdul Malik Hayat; Mahjabeen Masood; Saman Chaudhry; Awais Ahmed; Rashid Rasheed; Mehwish Nizam; Adnan Arshad (Radiology Case Reports)
Tri-orchidism which means 3 testes in the scrotal cavity, is the most common type of the polyorchidism. It is the rarest anomaly of the urogenital tract, and occurs more commonly on the left side. Superanumerary testes shows scrotal and extra-scrotal presentation and is associated with several clinical features and complications. We report a case of triorchidism in a 29-year-old man who presented with left hemiscrotal pain, later on diagnosed on clinical and sonographic examinations. The management depends on different factors and include conservative treatment with follow up, orchidopexy and orchidectomy. Orchidectomy is advised in suspected case of malignancy.